Boron enhances adaptive responses and biological performance via hormetic mechanisms. (1st May 2023) - Calabrese, Edward; Pressman, Peter; Agathokleous, Evgenios; Dhawan, Gaurav; Kapoor, Rachna; Calabrese, Vittorio
Abstract: Boron is shown in the present review to induce hormetic dose responses in a broad range of biological models, organ systems and endpoints. Of particular importance is that numerous hormetic findings have been reported with whole animal studies, with extensive dose response evaluations with the optimal dosing being similar across multiple organ systems. These findings appear to be underappreciated and suggest that boron may have clinically significant systemic effects beyond that of its putative and more subtle essentiality functions. The re-exploration of boron's bioactivity as seen through hormetic mechanisms may also underscore the value of this approach to the assessment of micronutrient effects in human health and disease. Graphical abstract: Representation of the hormetic dose response. Image 1 Highlights: Boron induced hormesis in a broad range of biological models. The hormetic effects of boron compliments its essentiality function. Boron induced optimal hormetic effects in multiple organs occur at the same dose. The hormetic effects of boron have potentially profound public health implications.